Awareness of Big Data in Select Sectors in Hyderabad; India - et. al., A.Rajini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big data produces massive content of accelerated information with variety and in less time by using advanced technology and various meticulous methods for converting the information produced by big data into value. The study aims to analyze the big data awareness amongst the employees in various sectors, investigate different management practices on developing a better strategy in the implementation of big data and study the impact of factors on organization culture in the implementation of big data. Probability random sampling adopted and data analyzed using Chi-square, ANOVA, and Stepwise regression analysis. The survey shows the impact of different select management practices on developing a better strategy in the execution of massive amount of data the Management Practices and Company Strategy is mostly influenced with Support by top level management. Thus, the research hypothesis proves that there is a significant relationship Management Practices and Company Strategies. Thus, the organization culture is mostly influenced by the Cost of data and the Difficulties of data. Therefore, the research hypothesis states that there is a significant relationship between various factors and culture of an organization.